1990
DOI: 10.1126/science.2106160
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Histone H4: Essential Role of Lysines Subject to Reversible Acetylation

Abstract: The nucleosome is the fundamental unit of assembly of the chromosome and reversible modifications of the histones have been suggested to be important in many aspects of nucleosome function. The structure-function relations of the amino-terminal domain of yeast histone H4 were examined by the creation of directed point mutations. The four lysines subject to reversible acetylation were essential for histone function as the substitution of arginine or asparagine at these four positions was lethal. No single lysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
275
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(291 citation statements)
references
References 33 publications
16
275
0
Order By: Relevance
“…Deletion mutants in the C‐terminus (Δ648–757 and Δ655–662) significantly blunted SIRT1‐dependent autophagy induction, while N‐terminal mutations (Δ2–92 and Δ262–392) did not (Figure 6b), indicating integral roles of the C‐terminus of MFN2 in SIRT1‐mediated induction of autophagy. To specify C‐terminal Lys residues that are functionally tied to autophagy enhancement, point mutants were generated to mimic Lys deacetylation by substituting Lys with arginine (Arg), which conserves the net positive charge of Lys but prevents charge neutralization by acetylation (Megee, Morgan, Mittman & Smith, 1990). As the C‐terminal sequence between 648 and 757 is likely involved in SIRT1‐dependent autophagy, we reasoned that K‐to‐R substitution in the C‐terminus would enhance autophagy even without SIRT1 overexpression.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion mutants in the C‐terminus (Δ648–757 and Δ655–662) significantly blunted SIRT1‐dependent autophagy induction, while N‐terminal mutations (Δ2–92 and Δ262–392) did not (Figure 6b), indicating integral roles of the C‐terminus of MFN2 in SIRT1‐mediated induction of autophagy. To specify C‐terminal Lys residues that are functionally tied to autophagy enhancement, point mutants were generated to mimic Lys deacetylation by substituting Lys with arginine (Arg), which conserves the net positive charge of Lys but prevents charge neutralization by acetylation (Megee, Morgan, Mittman & Smith, 1990). As the C‐terminal sequence between 648 and 757 is likely involved in SIRT1‐dependent autophagy, we reasoned that K‐to‐R substitution in the C‐terminus would enhance autophagy even without SIRT1 overexpression.…”
Section: Resultsmentioning
confidence: 99%
“…However, the K16 mutation to arginine is apparently the only single mutation that shows a clear significant increase in Sphase length (around 10 min longer) and a decrease in G 2 /M (around 7 min) (Megee et al, 1990(Megee et al, , 1995.…”
Section: Histone H4 Lysine 16 Acetylationmentioning
confidence: 97%
“…tail is dispensable for viability in yeast (Kayne et al, 1988), its loss is associated with defects in transcription (Durrin et al, 1991), cell-cycle progression (Megee et al, 1990), DNA repair (Bird et al, 2002), silencing (Johnson et al, 1990), and mating efficiency (Kayne et al, 1988;Park and Szostak, 1990). This requirement for the H4 tail lies in its four acetylatable lysines, as single substitution mutations of these lysines to either glutamine or arginine (which mimic acetylated or deacetylated lysine, respectively) show quite different outputs (Park and Szostak, 1990).…”
Section: Histone H4 Lysine 16 Acetylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential role of the acetylation of histone H4 lysines and its importance in maintaining the genome integrity came from three studies in the early 1990s. These studies showed that cells bearing several different mutations in the N termini of histone H4 exhibit cell cycle arrest at G 2 /M phase and compromised genomic stability (Megee et al, 1990(Megee et al, , 1995Durrin et al, 1991;Morgan et al, 1991). However, one of the first evidences of the involvement of histone acetylation in DNA repair was provided by Nakatani and collaborators who showed that Tip60 HAT was involved in DNA repair and that mutations in the acetylase activity of Tip60 resulted in cells with deficient DNA repair (Ikura et al, 2000).…”
Section: Dna Repairmentioning
confidence: 99%